Menuju Pembelajaran Madrasah yang Lebih Efektif: Sebuah Solusi dan Pendekatan Baru - M. Afiqul Adib (PT. Global Pustaka Ilmiah, 2024)
This research aims to explore solutions and new approaches towards more effective learning in madrasahs. A thorough literature review was conducted to analyze trends and key concepts in effective learning within the context of madrasah education. The literature analysis identified major challenges faced by madrasahs, including an excessive number of subjects, lack of development in critical, creative, and innovative thinking skills, as well as inadequate proficiency in information technology. Based on this analysis, the research proposes several solutions and new approaches. Evaluation of the proposed solutions is also conducted to assess the potential success of their implementation. The findings of this research are expected to provide significant contributions to the development of more effective learning in madrasahs.